Cystoisospora belli Gallbladder Infection in a Liver Transplant Donor - Clifford Akateh; Christina A. Arnold; Dathe Benissan-Messan; Anthony Michaels; Sylvester M. Black (Case Reports in Infectious Diseases)
Introduction. Cystoisospora belli (previously Isospora belli) is a parasitic protozoan of the human gastrointestinal system. It rarely causes symptoms in immunocompetent hosts but can cause severe diarrhea in immunocompromised patients, with a rate of recurrence and risk of dissemination. Gallbladder infections are however rare. The treatment of choice for symptomatic patients is a 7–10-day course of trimethoprim-sulfamethoxazole. Case. In this case, we report on an incidental finding of Cystoisospora belli organisms in the donor gallbladder following a transplant cholecystectomy. There was no report of symptoms in the donor. The recipient was treated with a course of trimethoprim-sulfamethoxazole, without evidence of cystoisosporiasis. Given the risk of recurrence in immunocompromised hosts, the patient will continue to be monitored for reactivation in the future. Conclusion. Despite advances in transplant protocols and screening, disease transmission from the donor to recipient still occurs in about 0.2% of all organ transplants. With the increased use of organs from drug overdose victims and other high-risk donors, practitioners (including pathologists, hepatologists, and surgeons) must maintain a high index of suspicion for such potentially harmful organisms.